Pemanfaatan Aplikasi Google sebagai Media Pembelajaran pada Mata Kuliah Pancasila - Iis Dewi Lestari (SAP (Susunan Artikel Pendidikan), 2021)
Various online learning media has become an option for lecturers during online learning. Choosing the right learning media needs to be taken carefully in accordance with the needs and the characters of students and lecturers. Google application has been chosen by many lecturers during online learning. Lecturers of Pancasila course in the Informatics Engineering study program use Google application to support Pancasila learning. The purpose of this study is to describe the use of the Google application in Pancasila course and to see the advantages and disadvantages of google application in online learning. The method used was descriptive qualitative. The subjects of this study were students and lecturers of Pancasila course in Informatics Engineering study program. The data techniques were observation, interview and documentation. Data analysis techniques were data reductions, data presentations and conclusions. The result of this research discovered that Google application was very helpful for online learning in Pancasila courses because through google application, lecturers and students were able to discuss virtually through Google Meet, collect assignments through Classrooms, and list attendance using Google Forms. The lack of Google application were there was no notification of how many students had downloaded material or videos, and it was only limited to the user of the Google account.